The Effect of Intellectual Capital and Early Warning System on the Profitability of Insurance Companies - Adam, Mukhtar A.; Fatah, Risalsa F.; Zainuddin, Zainuddin; Nurdin, Nurdin (LLDIKTI Wilayah 1 Sumatera Utara, 2025)
The insurance industry plays a crucial role in the economy by helping individuals and institutions manage financial risk. To maintain public trust, insurance companies must demonstrate strong financial performance, particularly in terms of profitability. This study aims to investigate the effect of Intellectual Capital, Firm Size, Early Warning System, Risk-Based Capital, and Investment Returns on the profitability of insurance companies in Indonesia. This quantitative study uses panel data from 25 insurance companies listed on the Indonesia Stock Exchange (I”X) and registered with the Financial Services Authority (OJK) during the 2019–2023 period. The data were analyzed using multiple linear regression with Eviews 13. The results indicate that Intellectual Capital, Firm Size, and Investment Returns have a significant positive effect on profitability. In contrast, Liquidity Ratio, Fund Adequacy Ratio, Claim Load Ratio, Premium Growth Ratio, Self-Retention Ratio, and Risk-Based Capital show no significant effect. These findings contribute to the understanding of financial drivers of profitability in the insurance sector and provide practical insights for improving investment strategy and risk management practices.